Important Functional Aspects on Face Transplantation. Current Literature Review - Victor Mario Martinez Bravo; José Fernando Montiel Castañeda; Homar Arnoldo Tanori Saavedra; Jesús Omar Ruiz Quiroz; Luis Fernando Ochoa Meza; Francisco Daniel Lara Ortiz; Alejandro Rodríguez López; Alfredo Gallardo Carreon; Teresita Ivett Muñoz Flores (International Journal of Medical Science and Clinical Research Studies, 2024)
Patients who suffer severe facial trauma not only face the burden of social isolation due to disfigurement, but they also frequently lose the ability to breathe on their own, eat without the use of substantial accommodations like straws or pureed food, or communicate verbally or through expressions. FT may be beneficial in improving quality of life and may even be able to avert potentially fatal consequences. To overcome the experimental nature of FT and strengthen evidence, future outcome reports should include information on problems and the capacity to smell, breathe, eat, speak, grimace, and feel facial sensations before and after FT. Unfortunately, many data are lacking from these reports.